1997
DOI: 10.1097/00001756-199708180-00021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for rapid face recognition from human scalp and intracranial electrodes

Abstract: It is still generally believed that complex visual analysis is not carried out within the first 100 ms. Here we show that intra- and extracranial visual evoked potentials (VEPs) differentiate previously seen faces from novel faces as early as 50 ms after stimulus onset. EEG was recorded from scalp electrodes in 12 male healthy volunteers (group I) and intracranially from implanted depth electrodes in the temporal and frontal cortex of seven epilepsy patients (group II). Both groups were engaged in a face recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
78
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 10 publications
20
78
0
1
Order By: Relevance
“…The visual percept was stronger for famous faces presented in the LVF (to the right hemisphere) than for famous faces presented in the RVF at short response latency (up to 500ms), with no difference at longer latencies; the visual percept strengthened from short to long latency trials for famous faces presented in the RVF, and showed no change for famous faces presented in the LVF. This pattern supports the proposition that the right hemisphere can construct a visual percept that distinguishes between famous and unfamiliar faces more rapidly than the left hemisphere (e.g., Seeck et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The visual percept was stronger for famous faces presented in the LVF (to the right hemisphere) than for famous faces presented in the RVF at short response latency (up to 500ms), with no difference at longer latencies; the visual percept strengthened from short to long latency trials for famous faces presented in the RVF, and showed no change for famous faces presented in the LVF. This pattern supports the proposition that the right hemisphere can construct a visual percept that distinguishes between famous and unfamiliar faces more rapidly than the left hemisphere (e.g., Seeck et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…However, things are not this simple. Seeck et al (1997) reported that early ERPs differed between famous and unfamiliar faces only in the right hemisphere, whereas later ERPs differed between famous and unfamiliar faces in both hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…As outlined in several studies, perception of a repeated (vs novel) face elicits a differential response up to 90 ms, then no difference until 190 -200 ms, and then again up to 600 ms (18,19,39,63). One could imagine that a rough analysis of the visual stimulus is carried out early in the processing.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover; the EPs obtained from patients with depth electrodes (43) (group II) were reanalyzed with special reference to early components (63). While the patients performed only at chance level, the normal subjects found the task also relatively difficult although the error rate was lower (about 6%).…”
Section: The Speed Of Face Recognitionmentioning
confidence: 99%
“…Linkenkaer-Hansen et al, 1998) as well as in intracranial ERP recordings in healthy subjects (e.g. Seeck et al, 1997;Krolak-Salmon et al, 2004). There is also recent interesting evidence of face cells in the pulvinar (Maior et al, 2010) and the superior colliculus (Nguyen et al, 2014), suggesting specific activations for faces beyond the classical striate pathway.…”
Section: Introductionmentioning
confidence: 97%